Nuclear IL-33 regulates cytokinesis and cell motility in normal human epidermal keratinocytes. Issue 2 (February 2022) - Tsuda, Hidetoshi; Tominaga, Shin-ichi; Ohtsuki, Mamitaro; Komine, Mayumi
Highlights: IL-33 is well known as an alarmin and a Th2 cytokine, but is now known as a nuclear protein to have influence on cell proliferation and cell division. We have demonstrated in this study that IL-33 promote cell proliferation and cell division in cultured normal human epidermal keratinocytes. IL-33 knockdown resulted in decreased BrdU incorporation and increased number of G2/M phase cells and binucleated cells. Supplementation of IL-33 restored the decreased BrdU incorporation and increased number of G2/M phase cells. IL-33 knockdown affected cell division and motility by slightly decreasing RhoA activity through decreasing ECT2 expression. Abstract: Background: IL-33 is a dual-functional molecule; it acts as a cytokine to enhance type 2 inflammation, and as a nuclear factor. The roles of nuclear IL-33 are not yet fully understood. Objective: We aimed to investigate the role of IL-33 in normal human epidermal keratinocytes (NHEKs). Methods: We utilized RNA interference to knock down cellular IL-33. Results: The IL-33 -knockdown (KD) cells showed decreased BrdU incorporation and decreasing tendency in RhoA activity and decreased ECT2 oncogene expression, compared to the controls. Supplementation of IL-33 expression utilizing adenovirus vector recovered the BrdU incorporation in IL-33 -KD cells. Increased number of G2/M phase cells and binucleated cells were observed among the KD cells. Overtime observation revealed that IL-33 -KD cells could not divide properly, formed binucleated cells, and were less motile than control cells. Conclusion: IL-33 KD in NHEKs affected the division and motility, probably by slightly decreasing the RhoA activity by attenuating ECT2 expression.